Imagining Collective Identities - Marine Poirier (Arabian Humanities)
Throughout the General People’s Congress (GPC) sustained course in office, its representatives have adjusted to multiple and often contradictory injunctions, adapting the organization’s discourse and activities to evolving situations and configurations of power. The aim of this article is to discuss the paradoxical accommodation of GPC’s institutional discourse during the last decade, in a context characterized by growing international pressures and the emergence, within the country, of competing political narratives. Although bound by external obligations and influences resulting from the circulation not only of labor forces but also of ideological norms and policy guidelines, party representatives have endorsed a deliberately nationalist discourse of self‑legitimization and mobilization meant to obscure these dynamics of identity hybridization while simultaneously playing down internal contentions.